내도복 다수성 검정깨 신품종 ‘윤흑’ - 심강보(Kang-Bo Shim); 황정동(Chung-Dong Hwang); 배석복(Suk-Bok Pae); 이명희(Myoung-Hee Lee); 정찬식(Chan-Sik Jung); 하태정(Tae-Jung Ha); 박금룡(Keum-Yong Park); 노재환(Jae-Whan Rho); 송득영(Duk-Young Song); 이세종(Se-Jong Lee); 남상영(Sang-Young Nam); 이재철(Jae-Chul Lee); et al. (Korean journal of breeding, 2011)
윤흑'은 내병성이 개선되고 다수성인 품종을 육성하기 위하여 다수성 계통인 유성깨에 고품질 내병성인 건흑깨를 1995년에 인공교배하여 육성한 품종으로 6년간의 계통육성을 통하여 유망계통을 선발하고 2002년부터 3년간 생산력 검정시험을 거친 후 전국 9개의 지역에서 3년간의 적응시험을 통하여 선발된 것으로 '윤흑'은 수량성이 높고 내도복성이면서 검정색 착색도가 진하고 레놀렌산 함량이 많은 고품질 품종이다. 또한 우리나라 기후조건에서 단작 및 이모작형의 광 A new sesame variety 'Yunheuk' was developed from Yeongnam Agricultural Research Institute in 2007. A cross was made by 'Yoosung' with weak disease resistance and 'Kunheuk'with high yield capacity & quality, followed by pedigree selection, yield test and regional yield trial (RYT) by the sesame breeding team at the National Institute of Crop Science and Yeongnam Agricultural Research Institute up to 2007. The variety showed higher lodging resistance and more dark seed coloring rather than that of check variety 'Yangheuk' Average stem length and the number of capsules per plant is 118 cm, 79 cm respectively. Its 1,000 grains weight is about 2.67 g indicating 0.10 g lower than that of 'Yangheuk' and its oil content is about 46.4%. 'Yunheuk'also contains total 2.59 mg/g of such lignans as sesamin and sesamolin. And its dark color density (L* Value) of seed coat is 22.43 which was about 10% lower than that of check variety. The average yield of 'Yunheuk'was 99.9 kg per 10a at the national-wide regional performance.